A Luxury Tourist Destination in Housing for Tourist Purposes: A Study of the New Airbnb Luxe Platform in the Case of Marbella. - Carrasco-Santos, María Jesús; Peña-Romero, Andrea; Guerrero-Navarro, Daniel (MDPI, 2023)
Marbella has a wide range of luxury property rentals, which are the subject of study within the framework of the collaborative economy, where the Airbnb platform stands out as the most used channel. This research focuses on the analysis of the total number of luxury villas offered in Marbella by Airbnb Luxe and Luxury Retreats. The methodology was carried out in four phases: the first phase involved a review of the literature on tourism and luxury and a study of Marbella as a luxury destination. The second phase focused on the analysis of the types of accommodation that Marbella offers. The third phase focused on the collection of data from the analyzed platform: Airbnb Luxe and Luxury Retreats. Finally, qualitative research consisting of in-depth interviews with owners and real estate agents focused on the luxury sector in Marbella was carried out. The results obtained yield relevant conclusions: Marbella is one of the main luxury holiday destinations in Spain, and the most demanded type of luxe accommodation in Marbella is large luxury villas. The term ‘luxury’ can be subjective, referring to such things as the visible and non-visible aspects that determine the category of a luxury property, hence the need to carry out a study on the luxury segment to establish a precise definition.
Keywords: Coste y nivel de vida; Lujo; Turismo - Marbella; Airbnb; Marbella; Luxury accommodation; Tourism; Sharing economy